On-Skin Epidermal Electronics for Next-Generation Health Management - Xu, Jinbin; Chen, Xiaoliang; Li, Sheng; Luo, Yizhuo; Deng, Shizheng; Yang, Bo; Lv, Jian; Tian, Hongmiao; Li, Xiangming; Shao, Jinyou (Nano-Micro Letters, 2025)
Continuous monitoring of biosignals is essential for advancing early disease detection, personalized treatment, and health management. Flexible electronics, capable of accurately monitoring biosignals in daily life, have garnered considerable attention due to their softness, conformability, and biocompatibility. However, several challenges remain, including imperfect skin-device interfaces, limited breathability, and insufficient mechanoelectrical stability. On-skin epidermal electronics, distinguished by their excellent conformability, breathability, and mechanoelectrical robustness, offer a promising solution for high-fidelity, long-term health monitoring. These devices can seamlessly integrate with the human body, leading to transformative advancements in future personalized healthcare. This review provides a systematic examination of recent advancements in on-skin epidermal electronics, with particular emphasis on critical aspects including material science, structural design, desired properties, and practical applications. We explore various materials, considering their properties and the corresponding structural designs developed to construct high-performance epidermal electronics. We then discuss different approaches for achieving the desired device properties necessary for long-term health monitoring, including adhesiveness, breathability, and mechanoelectrical stability. Additionally, we summarize the diverse applications of these devices in monitoring biophysical and physiological signals. Finally, we address the challenges facing these devices and outline future prospects, offering insights into the ongoing development of on-skin epidermal electronics for long-term health monitoring. Highlights: 1 This review comprehensively examines representative functional materials, analyzes their intrinsic properties, and illustrates how rational structural design and fabrication strategies can be employed to achieve high-performance epidermal electronics. 2 Three essential performance requirements for long-term, continuous health monitoring—adhesiveness, breathability, and mechanoelectrical stability—are emphasized, alongside effective strategies for their realization. 3 Current scientific challenges in this field are critically discussed, offering in-depth insights into the development of next-generation on-skin epidermal electronics aimed at transforming personalized healthcare.